Plant‐Based Diets Are Associated With a Lower Risk of Incident Cardiovascular Disease, Cardiovascular Disease Mortality, and All‐Cause Mortality in a General Population of Middle‐Aged Adults. Issue 16 (20th August 2019) - Kim, Hyunju; Caulfield, Laura E.; Garcia‐Larsen, Vanessa; Steffen, Lyn M.; Coresh, Josef; Rebholz, Casey M.
Abstract : Background: Previous studies have documented the cardiometabolic health benefits of plant‐based diets; however, these studies were conducted in selected study populations that had narrow generalizability. Methods and Results: We used data from a community‐based cohort of middle‐aged adults (n=12 168) in the ARIC (Atherosclerosis Risk in Communities) study who were followed up from 1987 through 2016. Participants' diet was classified using 4 diet indexes. In the overall plant‐based diet index and provegetarian diet index, higher intakes of all or selected plant foods received higher scores; in the healthy plant‐based diet index, higher intakes of only the healthy plant foods received higher scores; in the less healthy plant‐based diet index, higher intakes of only the less healthy plant foods received higher scores. In all indexes, higher intakes of animal foods received lower scores. Results from Cox proportional hazards models showed that participants in the highest versus lowest quintile for adherence to overall plant‐based diet index or provegetarian diet had a 16%, 31% to 32%, and 18% to 25% lower risk of cardiovascular disease, cardiovascular disease mortality, and all‐cause mortality, respectively, after adjusting for important confounders (all P <0.05 for trend). Higher adherence to a healthy plant‐based diet index was associated with a 19% and 11% lower risk of cardiovascular disease mortality and all‐cause mortality, respectively, but not incident cardiovascular disease ( P <0.05 for trend). No associations were observed between the less healthy plant‐based diet index and the outcomes. Conclusions: Diets higher in plant foods and lower in animal foods were associated with a lower risk of cardiovascular morbidity and mortality in a general population.